Linking Market Orientation to Patient Satisfaction: The Serial Mediation of Online Service Innovation and Web Design Quality - Graceallah, Georgerius; Lie Heng; Dewi Santika (Jurnal Manajemen, 2026)
This study aims to investigate the impact of market orientation strategies on consumer satisfaction, with online service innovation and web design quality serving as mediating variables. The purpose of this study is to explain the relationship between the use of market orientation strategies and the creation of consumer satisfaction through the mediation variables of online service innovation and web design quality. The form of research uses associative methods. The sample was determined using the purposive sampling technique with the criteria of consumers who are registered as domiciled in Pontianak City and have been Prodia's subscribers for more than 3 years. Respondents were assigned as many as 160 people using the multivariate technique, analyzed using the SEM method through the AMOS application. From the test results, it was obtained that H1 was accepted, where market orientation had a positive and significant effect on online service innovation; then H2 was accepted, where market orientation had a positive and significant effect on design quality; then H4 was accepted, where online service innovation had a positive and significant effect on consumer satisfaction. Different results were obtained where H3 was rejected, where the design quality did not have a significant effect on consumer satisfaction, and then H5 was also rejected, where market orientation did not have a significant effect on consumer satisfaction.